Application of composite materials based on polyvinyl alcohol in phytoremediation soil - Abduletip, D.T.; Urkimbayeva, P.I.; Mun, G.A.; Kenessova, Z.A.; Khavilhairat, B. (KSU Publ., 2020)
Oil production, transportation, transshipment and storage lead to accidental soil pollution with oil products. To solve this problem, the researchers proposed the possibility of using polymer films for the rehabilitation of oilcontaminated soils. In the present work, in order to clean the soil from oil products, films based on polyvinyl alcohol and chitosan were obtained, their main physical and mechanical properties were investigated. The results of IR spectrometric analysis showed good compatibility of the starting components. It was found that the films obtained possess rather high indices of mechanical strength. Moreover, films containing 80 % synthetic polymer — PVA showed the highest mechanical properties. The latter is apparently associated with the formation of a network of intermolecular hydrogen bonds between chitosan and PVA, which favorably affects their operational characteristics. Pollution modeling was carried out by applying oil to the soil of the Karazhanbass field. The resulting films based on polyvinyl alcohol and chitosan were used as recultivates, which were applied in concentrations of 0.2 g/kg of soil. The effectiveness of remediation of oil-contaminated soils was evaluated by measuring the content of oil products and conducting phytotests of the studied soil samples. The results of the assessment of the degradation of oil products in the process of reclamation and the phytotesting indicators obtained in the dynamics of the experiment allow us to conclude the effectiveness and feasibility of using polymer films based on polyvinyl alcohol and chitosan to clean oil-contaminated soils.
Поливинил спирті негізіндегі композициялық материалдарды топырақ фиторемедиациясында қолдану
Применение композиционных материалов на основе поливинилового спирта в фиторемедиации почв
Keywords: polyvinyl alcohol; chitosan; glycerol; polymer films; oil-contaminated soils; oil products; phytoremediation; remediation